Search for new physics in the dijet invariant mass spectrum at 8 TeV - Pachal, KE (2015)
A search for resonance signals from new physics models was performed using the ATLAS dijet invariant mass spectrum at a center-of-mass energy of 8 TeV. The full dataset from the 2012 data-taking period was used, corresponding to an integrated luminosity of 20.3 fb−1. The analysis covered a mass range from 250 GeV to 4.5 TeV and found no evidence of an excess anywhere in the spectrum. Upper mass limits were set at 95% CL on both model- specific benchmark new physics signals and on two different generic resonance forms: a Gaussian shape and a Breit-Wigner shape which accounted for pdf and detector effects. The analysis excluded excited quarks below 4.06, heavy W' bosons below 2.45, colour-octet scalars below 2.70, leptophobic chiral excited bosons W* below 1.75, and quantum black holes below 5.66 and 5.62 for the Qbh and BlackMax generators respectively.